Non-legal rules: problems of their determination and enforcement (theoretical aspect) - S. Biryukov; T. Biryukova (Правоприменение, 2018)
The subject of the paper is the approaches to the concept of “non-legal rules”.The main aim of the paper is to confirm or disprove the hypothesis that rules become non-legal when they contradict the principles of law and are totally ineffective.The description of methodology. The authors apply methodology of different legal theories: natural law, libertarian-legal, sociological, communicative, normative and integrative approaches to law, using formal logical and sociological research methods (observation method).The formal-legal method is also used with regard to characteristics of particular Russian laws.The main results and scope of their application. Legal rule may be unlawful for an external observer – in coordinates of another legal system or in comparison with law in a social sense. From the point of view of the internal observer, including the law enforcer, the following rules are non-legal: 1) regulations that were adopted, but initially or later it was officially recognized that they contradict the principles of law and the rules of higher legal force; 2) rules that could not be applied principally or that were not implemented until their cancellation.Many rules widely assessed as unfair, immoral, not consistent with the principles of law could be a part of the current system of law for a long time and could not be officially qualified as defective. Most of the very ineffective rules are still implemented selectively, some of them become quite effective in the future. Rules that are obviously not in conformity with acts of higher legal force may not be recognized as illegal officially because of various reasons. All of the non-legal rules, however, are very problematic for the law enforcement officials in several respects:– they may come into conflict with other regulatory systems of social regulation, including other social law of large (significant) groups and organizations, such situation entails difficulties in their legitimation and implementation;– they may come into conflict with other acts (rules, legal principles) within this or a related system of legal law;– they can be canceled (invalidated) in future, inter alia from the moment of their adoption.Conclusions. Rules are also potentially illegal, when they: 1) clearly contradict the principles of law and the rules of higher legal force; 2) are extremely ineffective. Such acts of lawmaking are very problematic from the point of view of their legitimation and implementation. Such acts are relatively common in Russian reality. The orientation of the practice to check their legal nature within the framework of the norm control is important for movement towards effective, fair and non-contradictory law, and not in the opposite direction.